Phantoms of Chittagong : the "Fifth Army" in Bangladesh - Uban, Sujan Singh (New Delhi : Allied Publishers, 1985)
On the military exploits of the Indian Special Frontier Force known as the Phantoms of Chittagong and the Fifth Army, led by the author in the India-Pakistan war, 1971.
Autobiographical.
Includes index.
Keywords: Uban, Sujan Singh; India. -- Army. -- Special Frontier Force -- History; India-Pakistan Conflict, 1971 -- Regimental histories; India-Pakistan Conflict, 1971 -- Personal narratives, East Indian